2013
DOI: 10.1186/1471-2121-14-47
|View full text |Cite
|
Sign up to set email alerts
|

New insights in osteogenic differentiation revealed by mass spectrometric assessment of phosphorylated substrates in murine skin mesenchymal cells

Abstract: BackgroundBone fractures and loss represent significant costs for the public health system and often affect the patients quality of life, therefore, understanding the molecular basis for bone regeneration is essential. Cytokines, such as IL-6, IL-10 and TNFα, secreted by inflammatory cells at the lesion site, at the very beginning of the repair process, act as chemotactic factors for mesenchymal stem cells, which proliferate and differentiate into osteoblasts through the autocrine and paracrine action of bone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 63 publications
4
10
0
Order By: Relevance
“…The observations from SWATH-MS analysis are strictly in accordance with previous observations concerning the upregulation of transcription factors and DNA-binding motifs in osteoblast differentiation process [Halcsik et al, 2013] as well as the important modifications of cell metabolism of cells undergoing osteogenic pathway [Hakelien et al, 2014].…”
Section: Discussionsupporting
confidence: 90%
“…The observations from SWATH-MS analysis are strictly in accordance with previous observations concerning the upregulation of transcription factors and DNA-binding motifs in osteoblast differentiation process [Halcsik et al, 2013] as well as the important modifications of cell metabolism of cells undergoing osteogenic pathway [Hakelien et al, 2014].…”
Section: Discussionsupporting
confidence: 90%
“…The involvement of these MAPKs has been observed in different osteogenic in vitro models (Gallea et al, 2001 ; Viñals et al, 2002 ; Guicheux et al, 2003 ). A recent report showed that p38 was predicted to account for 20% of the phospho-residues identified after treatment of MSCs with BMP (Halcsik et al, 2013 ). TGF-β provokes the phosphorylation of p38, ERK and JNK in a very rapid manner in MC3T3 and primary osteoblasts (Arnott et al, 2008 ).…”
Section: Signaling Triggers P38 In Osteoblast Functionmentioning
confidence: 99%
“…Osteogenesis was also addressed and achieved, being corroborated by Alizarin Red positive staining and increased levels of alkaline phosphatase mRNA, two standard methods for this type of differentiation. In addition, these cells also show a typical osteogenecic-associated phosphorylation pattern when inquired through phosphoproteomics [ 19 ]. Chondrogenesis was screened by Toluidine blue staining and collagen type II expression, with both parameters being positive in our model, suggesting that chondrocyte-like cells were obtained.…”
Section: Discussionmentioning
confidence: 99%
“…Chondrogenesis: DMEM-F12 (Gibco, Rockville, MD) 3:1, 0.5ug/ml Insulin (catalog number # I1882-100MG, Invitrogen, USA), 50uM ascorbic acid (catalog number # A4544-25G, Sigma, USA), 10ng/mL TGFβ-1 (catalog number # 7666-MB-005, R&D Systems, USA) and 1mM sodium piruvate (catalog number # 11360–070, Sigma, USA). Osteogenesis: αMEM (Gibco, Rockville, MD), 10% FBS, 0.1uM dexamethasone (catalog number # D4902-25MG, Sigma, USA), 2mM ascorbic acid (catalog number # A4544-25G, Sigma, USA), and 10mM Glycerol 2-Phosphate (catalog number # G9422-10G, Sigma, USA) as described in [ 19 ].…”
Section: Methodsmentioning
confidence: 99%